Urban–Rural Differences in Physical Activity in Belgian Adults and the Importance of Psychosocial Factors - Dyck, Delfien Van; Cardon, Greet; Deforche, Benedicte; De Bourdeaudhuij, Ilse (Journal of urban health, 2011)
Recent research in urban planning and public health has drawn attention to the associations between urban form and physical activity in adults. Because little is known on the urban–rural differences in physical activity, the main aims of the present study were to examine differences in physical activity between urban and rural adults and to investigate the moderating effects of the physical environment on the relationship between psychosocial factors and physical activity. In Flanders, Belgium, five rural and five urban neighborhoods were selected. A sample of 350 adults (20–65 years of age; 35 adults per neighborhood) participated in the study. Participants wore a pedometer for 7 days, and self-reported physical activity and psychosocial data were also collected. Results showed that urban adults took more steps/day and reported more walking and cycling for transport in the neighborhood, more recreational walking in the neighborhood, and more walking for transportation outside the neighborhood than rural adults. Rural adults reported more recreational cycling in the neighborhoods. The physical environment was a significant moderator of the associations between several psychosocial factors (modeling from family, self-efficacy, and perceived barriers) and physical activity. In rural participants, adults with psychosocial scores above average were more physically active, whereas there were no differences in physical activity according to psychosocial factors in urban participants. These results are promising and plead for the development of multidimensional interventions, targeting specific population subgroups. In rural environments, where changing the environment would be a very challenging task, interventions focusing on modifiable psychosocial constructs could possibly be effective.